Peningkatan Aktivitas Belajar IPA Siswa Kelas VII 2 SMP Negeri 2 Batang Anai dengan Menerapkan Strategi Pembelajaran Aktif Tipe GQGA - Syahrial, Syahrial; Lefita, Lefita; Erlinda, Nelfi (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
This research is background by the low of student activity in learning IPA for VII.2 class student of SMPN 2 Batang Anai. The causes are the teacher still lack of using interesting learning strategies. The lack of student desire to repeat the lesson has been given at the school, so it is difficult to understand by the student. Consequently the result of student learning is low. One of the way in improving the student active learning is to implement active learning strategies through the type of Giving Question and Getting Answer (GQGA). The purpose of this research is to improve the student activity in learning IPA for VII.2 class students of SMPN 2 Batang Anai through the type of GQGA.The kind of the research is action class research. The subject of this research is VII.2 class students of SMPN 2 Batang Anai who registered in period of 2015/2016. The instrument of this research was observation sheet in each meeting into two cyclus for student activity learning data, and result of final test in each final cyclus for result student learning data. Data analysis is like quantity analysis by using observation sheet, consist of positive and negative activities indicator student as long as learning in the class. Based on the data analysis is gotten the improve of student activities learning in positive indicator from 68% to cyclus 1 become 90% to cyclus 2. It influence to improve the student test achievement in percent in each final cyclus from 59% to cyclus 1 become 100% to cyclus 2. It can concluded there is improvement of the student activity in learning IPA for VII.2 class student of SMPN 2 Batang Anai through strategy active learning by the type of GQGA.